2023
DOI: 10.1155/2023/8888248
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Nano-ZnO Modified Asphalt and Its Influence on Moisture-Sensitive Properties of Mixtures

Abstract: This study investigates the effect of nano-ZnO on modified asphalt’s adhesion characteristics by preparing various mixtures with 0%, 1%, 2%, and 3% nano-ZnO contents. Within the study context, the adhesion characteristics of asphalt mixtures with different nano-ZnO to limestone, basalt, and granite contents are studied using a boiling test. The surface-free energy (SFE) parameters of four asphalt and three aggregate types are evaluated using a theoretical approach and then verified by performing pull-off tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The ZnO/SBS, carbon nano-tubes/SBS, crumb rubber/SBS, nano-organic palyorskite/SBS et al modification methods were conducted on asphalt, and the effect on the properties of asphalt had been verified by laboratory tests [14][15][16][17][18][19]. Chen investigated the impact of nano-ZnO on modified asphalt's adhesion characteristics by preparing mixtures with different modifier contents, and the results showed that nano-ZnO enhanced the moisture sensitivity and impacted the tensile strength and cracks resistance of asphalt mixtures [20]. Sina considered the influence of acidic contaminants on asphalt pavement, prepared porous asphalt mixtures with nano-ZnO and nano-silica and conducted mechanical performance tests on mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO/SBS, carbon nano-tubes/SBS, crumb rubber/SBS, nano-organic palyorskite/SBS et al modification methods were conducted on asphalt, and the effect on the properties of asphalt had been verified by laboratory tests [14][15][16][17][18][19]. Chen investigated the impact of nano-ZnO on modified asphalt's adhesion characteristics by preparing mixtures with different modifier contents, and the results showed that nano-ZnO enhanced the moisture sensitivity and impacted the tensile strength and cracks resistance of asphalt mixtures [20]. Sina considered the influence of acidic contaminants on asphalt pavement, prepared porous asphalt mixtures with nano-ZnO and nano-silica and conducted mechanical performance tests on mixtures.…”
Section: Introductionmentioning
confidence: 99%